M. G. Krein’s investigations in the theory of entire and meromorphic functions and their further development - Ostrovskii, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
This is a survey of М. G. Krein’s results in the theory of entire and meromorphic functions. Their further development is also discussed.